SERVICE EVALUATION OF A REAL- WORLD, DIGITALLY ENABLED, TIME RESTRICTED EATING PROGRAMME FOR ADULTS IN THE UK - Brown, Adrian; Patel, Dipesh; c, Jonathan; Steinmo, Siri; Eaton, Danielle; Falvey, Laura; Chow, Ling; McGowan, Barbara (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE Obesity and type 2 diabetes (T2D) remain global health challenges. Continuous energy restriction enables weight loss, but recently time-restricted eating (TRE) has gained traction. Limited data exists about its effectiveness in a real-world setting. Reset Health is a technology-enabled programme for people living with obesity and T2D delivered by clinicians and mentors. The aim of this service evaluation was to assess the impact of the Reset Health programme on weight, metabolic parameters, and other health-related outcomes. METHODOLOGY We enrolled 653 adults (mean age 46.3 ± 10.8 yrs, mean BMI 35.2 ± 6.4 kg/m2, HbA1c 42.4 ± 12.5 mmol/mol; 61% White Ethnicity) with 114 having pre- (n = 59; 9.0%) or T2D (n = 56; 8.6%). Data were analysed at 12 and 24-weeks of the 244 completers and reported using mean ± SD. RESULTS Members lost a significant amount of weight at 12- and 24-weeks, 7.7 ± 4.4 kg and 9.5 ± 5.9 kg respectively (p<0.001). Waist circumference decreased by 11 ± 7.5 cm at 24 weeks (p<0.001), with systolic blood pressure reducing by 6.6 ± 12.6 mm Hg (p<0.001) and diastolic blood pressure by 4.2 ± 10.5 mm Hg (p=0.002). HbA1c reduced by 4.5 ± 7.4 mmol/mol (p=0.05) in all participants and 8.7 ± 9.2 (p=0.07) in those with T2D. Quality of life improved over 24-weeks with significant reductions in depression (2.2 ± 3.4, p<0.001) and anxiety (1.9 ± 4.0; p<0.001) scores. Eating behaviour improved with a reduction in binge eating and emotional eating scores (5.9 ± 8.1; p<0.001; 0.69 ± 0.83, p<0.001, respectively), while restraint eating score increased (0.26 ± 0.62; p=0.001). CONCLUSION Evaluation of a novel service using a clinically led, digitally enabled time restricted eating programme within a real- world population shows significant improvements in weight loss, health-related outcomes and eating behaviour.